2014
DOI: 10.1063/1.4896361
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic power absorption due to bumps and trenches on flat surfaces

Abstract: This paper presents a study of the absorption of electromagnetic power that results from the interaction of electromagnetic waves and cylindrical bumps or trenches on flat conducting surfaces. Configurations are characterized by means of adequately selected dimensionless variables and parameters so that applicability to mathematically equivalent (but physically diverse) systems can be achieved easily. Electromagnetic fields and absorption increments caused by such surface defects are evaluated by means of a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…The contribution [17] is in fact much more general: in our method configurations are characterized by means of adequately selected structural elements so that physically diverse systems can be treated with minimal variations of a basic mathematical structure. Our studies of a variety of configurations [18] gave rise to interesting conclusions concerning the character of asperity-enhanced absorption. We found that typically absorption is enhanced by the presence of asperities, although, interestingly, absorption can also be significantly reduced in some cases-such as, e.g., in the case of a trench on a conducting plane where the incident electric field is perpendicular to the plane.…”
Section: Well-conditioned Integral Formulations and Algorithmsmentioning
confidence: 99%
See 3 more Smart Citations
“…The contribution [17] is in fact much more general: in our method configurations are characterized by means of adequately selected structural elements so that physically diverse systems can be treated with minimal variations of a basic mathematical structure. Our studies of a variety of configurations [18] gave rise to interesting conclusions concerning the character of asperity-enhanced absorption. We found that typically absorption is enhanced by the presence of asperities, although, interestingly, absorption can also be significantly reduced in some cases-such as, e.g., in the case of a trench on a conducting plane where the incident electric field is perpendicular to the plane.…”
Section: Well-conditioned Integral Formulations and Algorithmsmentioning
confidence: 99%
“…The contributions [17,18] concern electromagnetic scattering by asperities (bumps or cavities) on otherwise undisturbed planar regions. Relying on use of Sommerfeld integrals we thus developed integral solvers which enable accurate evaluation of energy absorption for asperities of arbitrary shape.…”
Section: Well-conditioned Integral Formulations and Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Joule heating limits the operation of most current carrying components and devices, ranging from large high power systems to nanoscale wires and devices. The coupled thermal-electrical conduction problem is important for wirearray Z-pinches, 1 power transmission lines, 2 high power microwave devices, 3,4 and electrical contacts. [5][6][7][8][9] In a Zpinch, in particular, coupled thermal-electrical conduction is responsible for an electrothermal instability.…”
Section: Introductionmentioning
confidence: 99%